Diagnóstico de comprensión lectora en adolescentes mediante aplicación de una prueba tipo saber basada en fábulas - Baquero Moreno, Leydit Ruth (Universidad Antonio Nariño, 2023)
In this work, a Saber type test was applied to a group of 20 young people in their last year of secondary education in a public educational institution, located in the town of Usme, Bogotá, Colombia, who studied between 4 and 12 years in the same. In the same way, a demographic characterization and an observation of reading habits in the classroom were carried out during specialized days of fable reading. We sought to differentiate reading comprehension processes of continuous and discontinuous texts, as well as demographic markers that explain positive or negative results compared to their reference group.